2019
DOI: 10.1002/chem.201901080
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonium‐Ring‐Fused Bicyclic Metallafuran Complexes of Ruthenium and Osmium

Abstract: Metallafuran complexes with a fused five‐membered phosphonium ring were synthesized from reactions between terminal ynones HC≡C(C=O)R and cis‐[Ru/Os(dppm)2Cl2] (dppm=1,1‐bis(diphenylphosphino)methane). A metal–vinylidene‐involving pathway was found to be an energetically feasible formation mechanism for these complexes. These phosphonium‐containing metallafurans, like many phosphonium‐functionalized drugs, have the ability to induce mitochondrial dysfunction. They also exhibit stronger cytotoxicity against sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 99 publications
0
12
0
Order By: Relevance
“…The formation of 11 a was rationalized to be derived from “non‐vinylidene‐involving” 5‐endo‐dig cyclization pathway (Scheme ). Performing the reaction at elevated temperature gave phosphonium‐ring‐fused osmafuran complex 11 b , which was established to be derived from “vinylidene‐involving” pathway …”
Section: Validating “Non‐vinylidene‐involving” Pathways Through Isolamentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of 11 a was rationalized to be derived from “non‐vinylidene‐involving” 5‐endo‐dig cyclization pathway (Scheme ). Performing the reaction at elevated temperature gave phosphonium‐ring‐fused osmafuran complex 11 b , which was established to be derived from “vinylidene‐involving” pathway …”
Section: Validating “Non‐vinylidene‐involving” Pathways Through Isolamentioning
confidence: 99%
“…Performing the reactiona te levated temperature gave phosphonium-ring-fused osmafuran complex 11 b, [40] which was established to be derived from "vinylidene-involving" pathway. [41]…”
Section: Catalytic Ru II -Mediated Cyclizations Of N/o-functionalizedmentioning
confidence: 99%
“…Although the formation of metal–vinylidene species via alkyne–vinylidene rearrangement has been regarded as a key step in Ru(II)-induced alkyne transformations, a number of our synthetic studies revealed that Ru(II) can also activate alkynes via “non-vinylidene” pathways [ 31 , 32 ]. With the aim to gain control on the modes of alkyne activation, we initiated research activities on probing and isolating intermediates and products from the reactions between functionalized alkynes and a variety of Fe(II), Ru(II) and Os(II) complexes [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. In 2015, we reported the synthesis of metallafuran complexes in the form of [M(bpy) 2 (C^O)] + from the reactions between cis -[M(bpy) 2 Cl 2 ] (M = Ru, Os; bpy = 2,2′-bipyridine) and ynone HC≡C(C=O)Ph in MeOH ( Scheme 1 a; C^O represents an anionic bidentate [ C (OMe)CHC(Ph) O ] − chelate, coordinating atoms in italics) [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our group has been investigating the reaction mechanisms between d 6 transition metal complexes and functional alkynes and reported the isolation of monocyclic or bicyclic metallafurans from the reactions between terminal ynone HCC­(C=O)­R and d 6 transition metal precursors including cis -[Ru­([14]­aneS4)­Cl 2 ], cis -[M­(bpy) 2 Cl 2 ], and cis -[M­(dppm) 2 Cl 2 ] (M = Ru and Os; [14]­aneS4 = 1,4,8,11-tetrathiacyclotetradecane; bpy = 2,2′-bipyridine; dppm = 1,1-bis­(diphenylphosphino)­methane). ,,, We herein report the isolation of indolizine-fused ruthenafuran and osmafuran complexes from the one-pot reactions between cis -[Ru II /Os II (dppm) 2 Cl 2 ] and dipicolinyl-substituted propargylic substrates HCCC­(OR)­(CH 2 (2-py)) 2 . Notably, these complexes not only represent an unprecedented class of metallafurans but also provide insights via their formation mechanism into Ru/Os-induced alkyne transformations.…”
Section: Introductionmentioning
confidence: 99%